Crop genetic diversity to reduce pests and diseases on-farm: Participatory diagnosis guidelines. Version I - Jarvis, Devra I.; Campilan, D.M. (2006)
Based on the outputs of the participants of the Spoleto, Italy (2002) Initial Planning Workshop, and the Kunming, China (September 2004) and Meknes, Morocco (March 2005) Workshops on Diagnostic Tools to Understand Farmers' Knowledge, Beliefs and Practices.